ANALISIS KESALAHAN MENYELESAIKAN SOAL MATEMATIKA DALAM MATERI MATRIKS PADA SISWA KELAS XI IPS SMA NEGERI 1 ENDE - Maria Angelina Weo Edo; Yasinta Yenita Dhiki; Konstantinus Denny Pareira Meke (Program Studi Pendidikan Matematika, 2021)
This study aims to determine: (1) mistakes have been made by the XI IPS grade students of SMA Negeri 1 Ende in solving matrix questions. (2) the factors that cause the XI IPS grade students of SMA Negeri 1 Ende in solving the matrix problem. (3) the efforts to solve students' errors in solving matrix questions in class XI IPS SMA Negeri 1 Ende. This study used a qualitative research approach using triangulation of sources and triangulation of techniques. The research subjects were 15 students of class XI IPS 3. The consideration of subject taking is based on the results of the error analysis according to the Newmann procedure. Methods of data collection using diagnostic tests, interviews, and documentation. The results of the research are: (1) the types of student errors are errors in understanding the concept of matrix count operations, process errors in solving matrix problems, and errors in concluding. 2) the factors that cause student errors are, students, choose the wrong formula, are not careful in solving matrix calculation operation problems, students are afraid to ask the teacher, and students' assumptions that mathematics is complicated, causing errors in determining the final answer. 3) while the efforts made were learning using rainbow matrix media which proved to be effective in learning matrix count operations.